A study of the selection of activity for the occupational therapy medium : Pretoria multimotivational therapeutic apparatus - Dyke, Anne Patricia (Stellenbosch : Stellenbosch University, 2012)
Teacher's Diploma in Occupational Therapy, University of Stellenbosch, 1972.